Livia Flores: ‘landscape exercises’ (Simbiótica. Revista Eletrônica, 2022)
The text addresses apprehensions of landscape in the works of the Brazilian contemporary artist Livia Flores that confront subject and territory, interior and exterior. In the article, we analyze, in addition to the artist's visual works, also her poetic collaborations - produced within the framework of the collective Anáguas -, as well as her research project in art and the city, entitled Desilha. To this end, we collate art, literature, philosophy and geography theorists, going through 'landscape exercises' triggered in the fields of fine arts, poetry and higher education.Keywords: Livia Flores; landscape; contemporary art; Brazilian art.